Devising a consensus definition and framework for non-technical skills in healthcare to support educational design: A modified Delphi study. (July 2015) - Gordon, Morris; Baker, Paul; Catchpole, Ken; Darbyshire, Daniel; Schocken, Dawn
Abstract: Background: Non-technical skills are a subset of human factors that focus on the individual and promote safety through teamwork and awareness. There is no widely adopted competency- or outcome-based framework for non-technical skills training in healthcare. The authors set out to devise such a framework using a modified Delphi approach. Methods: An exhaustive list of published and team suggested items was presented to the expert panel for ranking and to propose a definition. In the second round, a focused list was presented, as well as the proposed definition elements. The finalised framework was sent to the panel for review. Results: Sixteen experts participated. The final framework consists of 16 competencies for all and eight specific competencies for team leaders. The consensus definition describes non-technical skills as "a set of social (communication and team work) and cognitive (analytical and personal behaviour) skills that support high quality, safe, effective and efficient inter-professional care within the complex healthcare system". Conclusions: The authors have produced a new competency framework, through the works of an International expert panel, which is not discipline specific that can be used by curriculum developers, educational innovators and clinical teachers to support developments in the field.